نمذجة ومحاكاة الشبكات الضوئية (CWDM) بأربع قنوات باستخدام برنامج optisysytem - نعمة, سوزان; قداحة, هبة (Latakia University Journal -Engineering Sciences Series, 2016)
يتضمن هذا البحث محاكاة لمرسل ومستقبل التجميع الخشن بتقسيم طول الموجة CWDM (Coarse Wavelength Division Multiplexing) بأربع قنوات، حيث تمّت دراسة تأثير نسبة الإخماد ER (Extinction Ratio) لثنائي الليزر المعدّل بشكل مباشر DML (Directly Modulated Laser) وتأثير وجود مضخمات EDFA (Erbium Doped Fiber Amplifier) في وصلات الألياف الضوئية في معامل الجودة Q ونسبة خطأ البت BER عند استخدام أطوال ليف مختلفة، وأجريت مقارنة بين شبكة الـ CDWM باستخدام مضخم EDFA والشبكة ذاتها من دون استخدام المضخم EDFA ، كذلك تمّ دراسة تأثير طول الليف الضوئي على معامل الجودة Q بوجود مضخم EDFA وبعدم وجوده ووضحنا العلاقة بينهما بيانياً.This research involves a simulation of four channels coarse wavelength division multiplexing (CWDM) transceiver. The study is done on the effect of the extinction ratio(ER) of the directly modulated laser (DML) diode, the effect of using Erbium doped fiber amplifier (EDFA) in optical fiber links on the quality factor (Q) and the bit error ratio (BER) when using different lengths of fiber. Then a comparison is made between the CWDM network using the amplifier EDFA and the same network without using the amplifier EDFA. In addition, the study is done on the effect of optical fiber length on Q with and without the amplifier EDFA, and we demonstrated the relationship between them diagrammatically.